Mapping technology and GIS - Edwards, Larry J., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
Mapping technology, specifically photogrammetry and its related disciplines, has been extensively employed for irrigation and drainage engineering and management applications since becoming a practical tool in the post World War II era. The computer, space and information systems revolution of the '80's has radically changed the methods and potential for photogrammetric mapping applications. All aspects of photogrammetry have been affected including ground control surveys, aerial photography, stereo-restitution and map compilation, and cartography, the form in which maps are presented or published. The NAVSTAR Global Positioning System (GPS) satellites are used extensively to rapidly establish highly accurate ground for mapping projects. GPS is also used to improve aerial photography operations by providing an accurate flight line guidance system. Future GPS developments will permit instantaneous and highly accurate positioning of the aerial camera system at the moment of exposure. The analytical stereo plotting instrument developed and the close of the '50's is rapidly becoming the industry standard for the measurement and conversion of aerial photographs into highly precise maps and spatial data. The evolution of the personal computer and computer graphics has led to the "digital map" and the "digital terrain model" which in turn provides powerful management and analysis capabilities for geographically distributed data through the use of Geographic Information Systems (GIS).
Irrigation and water resources in the 1990's
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.